Low cost audio based intelligent guidance system for visually impaired people - Komal Venugopal, Vattumilli; Naveen, Alampally; .R, Rajkumar; K. , Govinda; Masih, Jolly (International Journal of Psychosocial Rehabilitation, 2020)
In this paper we are proposing the IoT-based intelligent guidance and navigation system for visually impaired persons with low cost. As a visually impaired person continuously requires assistance and monitoring of other people for their mobility, health, and routine, they are more dependent on other people. They can use only their senses, such as by sound or by feel and touch, and moreover, they use a stick to navigate, which is not much help. As they face issues in communicating easily with the surroundings. In order to solve the traveling issue, we are presenting a lightweight, intelligent guiding system in the shape of a pair of glasses, which will provide guidance properly. As IoT has changed the whole industry, our proposed system for the navigation system includes some sensors like an ultrasonic distance sensor, GPS, and a camera, which is being mounted on a Raspberry Pi board. This detects the obstacles in their path to navigate themselves in different locations efficiently and safely. The information about the obstacle and the text that is present in front of the user is being informed to the visually impaired person through an audio device, which can be earphones, and if any issue arises regarding the audio, which can be due to a noisy environment, the person is being informed through vibration. The camera module captures the object and informs the user what it is. This system continuously monitors the real-time environment to avoid the obstacles. Sensors play the key role in the whole system to detect and guide the visually impaired person.